Efficacy of Perfusion Computed Tomography (PCT) in Differentiating High-Grade Gliomas from Low Grade Gliomas, Lymphomas, Metastases and Abscess - Karegowda, Lakshmikanth Halegubbi (J Clin Diagn Res, 2017)
INTRODUCTION: Tumoural angioneogenesis and its quantification are important in predicting the tumour grade and in the management with respect to the treatment available and to assess the response to treatment and the prognosis. It also plays major role in the growth and spread of tumours. Hence, a need arises for non-invasive in vivo methods to assess tumour angioneogenesis and tumour grade at the time of presentation and for monitoring the response during treatment and follow up. In this regard Perfusion Computed Tomography (PCT) can be easily added into routine CT studies to obtain such information on lesion physiology along with its morphology. AIM: Prospective evaluation of the efficacy of PCT in differentiating high grade gliomas from low grade glioma lymphomas, metastases and abscess. MATERIALS AND METHODS: Perfusion CT was performed in 68 patients (17 high-grade gliomas, 10 low-grade gliomas, 7 lymphomas, 27 metastases and 7 abscess). Perfusion parameters which include Cerebral Blood Volume (CBV), Cerebral Blood Flow (CBF), Mean Transit Time (MTT) and Time To Peak (TTP) were derived both from the lesion and the normal parenchyma and were Normalized (n) by obtaining the ratio. Statistical analysis for high grade versus low-grade gliomas, high grade gliomas versus lymphomas, metastases and abscess was performed. RESULTS: Difference in the mean nCBV and nCBF in high grade gliomas were statistically significant from low grade gliomas with cut off of > 3.07 for nCBV and > 2.08 for nCBF yielding good sensitivity and specificity. Difference in the mean nCBV and nMTT in the lymphomas were statistically significant from high grade gliomas (p<0.05) with cut off of <3.40 for nCBV and >1.83 for nMTT yielding good sensitivity and specificity. Difference in the mean nCBV and nMTT in the metastases were statistically significant from high grade gliomas (p<0.05) with cut off of >4.95 for nCBV and >1.88 for nMTT yielding a fair sensitivity and specificity. No statistical significant difference seen among the parameters in differentiating high grade gliomas and abscess. CONCLUSION: Cerebral PCT greatly adds to the diagnostic accuracy when the diagnosis of a common intra-axial lesion based on morphological characters becomes uncertain.